Calculating RIP mutation in fungal genomes using RIPCAL - Hane, James (Springer, 2015)
Repeat-induced point mutation (RIP) occurs in some fungal taxa, preferentially mutating C:G nucleotide pairs that reside within repetitive DNA and converting them to T:A. Within the taxon Pezizomycotina, RIP is biased towards mutation of CpA dinucleotides. RIP is an important feature of fungal genomes as its distribution and extent have important implications for genome evolution. Early studies of RIP did not have access to vast amounts of genome sequence information; therefore RIP was measured within one or a handful of repeat sequences using ratios of dinucleotide frequencies. However as whole-genome sequences became available for fungi, it became possible to predict the repeat content of a whole genome and calculate RIP mutation across a large number of sequences from multiple repeat families. The software tool RIPCAL was developed for this purpose and since its release has become widely used in fungal genome analysis pipelines.